2020
DOI: 10.3390/ijerph17218210
|View full text |Cite
|
Sign up to set email alerts
|

Primitive Reflex Activity in Relation to the Sensory Profile in Healthy Preschool Children

Abstract: The presence of active primitive reflexes (APRs) in healthy preschool children can be an expression of immaturity in the functioning of the nervous system. Their trace presence may not significantly affect the quality of child functioning. They may also undergo spontaneous and complete integration within the stages of child development. However, a higher level of active reflexes and their significant number can disturb sensory-motor development and lead to additional problems in a child’s motor activities, soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…With the maturation of the central nervous system, these primitive reflexes become more challenging to evoke after the first year postpartum when the infant becomes capable of voluntary motor activity. RPRs are not infrequently present in children with ASD, ADHD, or cerebral palsy, and may be early indicators of brain-based deficits (3,4,22,148,(292)(293)(294)(295).…”
Section: Discussionmentioning
confidence: 99%
“…With the maturation of the central nervous system, these primitive reflexes become more challenging to evoke after the first year postpartum when the infant becomes capable of voluntary motor activity. RPRs are not infrequently present in children with ASD, ADHD, or cerebral palsy, and may be early indicators of brain-based deficits (3,4,22,148,(292)(293)(294)(295).…”
Section: Discussionmentioning
confidence: 99%
“…Searching new aspects of child development, working in new fields and using new tools to understand children in the process of growing up is one of the goals of the PRACS project. We analysed the neuromotor development of the children in the aspects of physical, social and educational status [ 8 , 20 , 21 , 22 , 24 ]. The presented article shows the results of the research connected with spatio-temporal gait parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The project investigates primitive reflexes and their impact on the motor, sensory, and cognitive development in preschool and school-age children. There are four articles published from the project so far [ 20 , 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…The most severe consequences of primary reflexes persistence are typically found in children with cerebral palsy, while milder persistence has been observed in children with reading difficulties and motor problems (McPhillips, Hepper & Mulhern, 2000). It has also been shown that the non-integration of primitive reflexes can cause developmental delays, and is associated with a variety of disorders, such as ADHD (Konicarova, Bob & Raboch, 2013), autism, learning difficulties (Bilbilaj, Gjipali & Shkurti, 2017;Hickey & Feldhacker, 2021;Matuszkiewicz & Ga lkowski, 2021), dyspraxia (Pecuch et al, 2020), dyslexia, behavioral disorders (Rashikj-Canevska & Mihajlovska, 2019) or sensory processing disorders (Bilbilaj et al, 2017, Rashikj-Canevska & Mihajlovska, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…If primary reflexes inhibition does not occur in a proper and orderly manner, children may develop, in addition to other difficulties, poor Motor Competence (MC) (Gieysztor, Choińska & Paprocka-Borowicz, 2018). Early signs of this may appear as difficulties in running, balance, aiming and catching tasks, poor visual coordination, lack of rhythm or defective spatial orientation (Gieysztor et al, 2018;Pecuch, Ko lcz-Trze˛sicka, Żurowska & Paprocka-Borowicz, 2018;Pecuch et al, 2020).…”
Section: Introductionmentioning
confidence: 99%